The origin of wealth matters: Equity norms trump equality norms in the ultimatum game with earned endowments - Barber, Benjamin; English, William (Elsevier, 2019)
We conduct an ultimatum game with three treatments: one in which endowments are earned through a real effort task (answering spelling questions under time pressure), one in which endowments are awarded through lotteries, and a standard ultimatum game with exogenously provided wealth. When subjects earn the money at stake, the modal response ceases to be an equal split, as proposals anchor around comparative earnings and these proposals are statistically different from those observed in the other treatments. Moreover, roughly half of lower earners propose keeping less than 50% of the pot for themselves. We argue that these results are best explained by Bicchieri’s account of norms and that equity, rather than equality, becomes the dominant norm in ultimatum bargaining when endowments are earned.
Keywords: Ultimatum game; Norms; Equity theory; Inequity aversion; Earned endowments; 53 Ciencias Económicas::5304 Actividad económica::5304.02 Distribución; ODS 10 - Reducción de las desigualdades